Inovaçao, conhecimento e aprendizagem : um estudo sobre Arranjos Produtivos Locais de erva-mate no sul do Brasil - Chechi, Leticia Andrea (Mundo Agrario.)
The objective of this study is to analyze the innovative dynamics of local productive arrangements of yerba mate in southern Brazil, from the learning processes, types of knowledge and interaction relations established among the actors. Two productive arrangements were defined, comprising three municipalities each, one being denominated RS productive Arrangement, and another Arrangement PR and SC. It was possible to comprehend that the innovative dynamics in the productive arrangements studied, respecting their specificities, is influenced mainly by the learning process by interaction, through the establishment of relations between local agents and the sharing of tacit knowledge of them.